Short Review of Orthopedics - Sabat Dhananjaya; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2010)
Over last few decades, this branch of medical science has seen a rapid progress in its horizons and entered into an era of sub-specialties. So to cover the whole Orthopedics in a small space was a herculean task. I worked over two years to make this book see the daylight. The whole text is written in a concise manner, highlighting important points. Tables and mnemonics are added to help the readers memorize the data. I consciously have given diagrams only wherever essential. In spite of all the efforts to keep the book error free, I feel some mistakes might have been overlooked. I request the readers to bring them to my notice, so that they can be rectified. Though the book is written targeting the students preparing for MBBS and pre-PG examinations, I still feel this will be of great help to PG, D-Orth and DNB Orthopedic students for their theory examinations too. The work will be a success the day it finds space on the desk of every student going for examination in Orthopedics.
Keywords: MCQs and Self-assessment,Orthopedics; Electronic books